(3Zfj hefj aj GdWHs - (3GdMSf Hf fhM GdbeQj GdMcje, CHh efUhQ,J (B380 (3g` s
(3ChdgG (B:s
(3bGd CHhefUhQ Efj de CQi aj UHGj hefP ZadJ CMH GdYdhe GdWHjYjI hJfGRYfi faSi EdjgG hNUhUkG Yde GdWH deG cfJ CQi ajg ef EQGMI GdCfaS s
(3BNQgG (B:s
(3bGd eMeO Hf RcQjG (B: (3jchf ef GdOjOGf GdUQY hGdLhY GdTOjO GdPi dGjScf, hjJHYg ZKi Ef de jCcd hNabGf GdbdH hhLYg , MJi QHeG bJd s
(3fSNI NGeSI JTJed Ydi GdfUa GdChd ef GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B166 s
Keywords: (3GdWHs